Mantle cell lymphoma in the era of precision medicine-diagnosis, biomarkers and therapeutic agents - Inamdar, Arati A. (Oncotarget, 2016)
Despite advances in the development of clinical agents for treating Mantle Cell Lymphoma (MCL), treatment of MCL remains a challenge due to complexity and frequent relapse associated with MCL. The incorporation of conventional and novel diagnostic approaches such as genomic sequencing have helped improve understanding of the pathogenesis of MCL, and have led to development of specific agents targeting signaling pathways that have recently been shown to be involved in MCL. In this review, we first provide a general overview of MCL and then discuss about the role of biomarkers in the pathogenesis, diagnosis, prognosis, and treatment for MCL. We attempt to discuss major biomarkers for MCL and highlight published and ongoing clinical trials in an effort to evaluate the dominant signaling pathways as drugable targets for treating MCL so as to determine the potential combination of drugs for both untreated and relapse/refractory cases. Our analysis indicates that incorporation of biomarkers is crucial for patient stratification and improve diagnosis and predictability of disease outcome thus help us in designing future precision therapies. The evidence indicates that a combination of conventional chemotherapeutic agents and novel drugs designed to target specific dysregulated signaling pathways can provide the effective therapeutic options for both untreated and relapse/refractory MCL.